Edu Fun Animation : Membuat Video Pembelajaran Menyenangkan Dengan Animasi Bagi Guru Excellent Mandiri School (Jurnal Pengabdian Masyarakat UNAMA, 2023)
With technological developments in the field of education today, teachers are required to be able to provide innovation in making appropriate learning media. The practical use of smartphones can support teachers in developing their learning media by making fun animated videos. Excellent Mandiri School is one of the private schools in Jambi City that has Kindergarten and Elementary school education, especially for Kindergarten students where the concept of playing and learning is important, so this learning medium with animated videos aims to be able to attract and direct students to concentrate on understanding the subject matter presented, as well as increase interest, pleasure, and interest when learning because it uses illustrated text. Based on observations made, Excellent Mandiri School teachers need training in developing learning media for their students, namely "Edu Fun Animation: Making Fun Learning Videos with Animations for Teachers (Excellent Mandiri School)" so that the material provided is interesting and can motivate students to understand the material presented, as well as improve the ability of teachers to innovate in making interesting technology-based learning media by utilizing smartphones as a supporting tool for making fun animated videos.